Low-friction compound gear as well as preparation method and application thereof
By introducing polyphenylene sulfide segment crystallizing agents and thermally conductive fibers into composite gears, crystallization is promoted and thermally conductive channels are constructed, thus solving the thermal deformation problem of polylaurolamide gears under high load and high temperature, and realizing composite gears with high thermal conductivity and high load capacity.
Patent Information
- Application Number
- CN202511604385.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-05
- Publication Date
- 2025-12-05
- Estimated Expiration
- 2045-11-05
AI Technical Summary
Existing polylauramide gears are prone to thermal deformation under high load and high temperature conditions, and have poor thermal conductivity, which limits their application in high-power transmission fields.
By combining polyphenylene sulfide segment crystallizing agent with thermally conductive fiber, polylaurolamide and polyoxymethylene are promoted to crystallize through primary crystal nuclei, thus constructing a highly crystalline composite gear. Thermally conductive channels are distributed in the resin matrix to form a "skin-core" structure to enhance thermal conductivity.
It improves the load-bearing capacity and thermal conductivity of composite gears, enhances their mechanical properties, prevents heat accumulation, and extends their service life.
Smart Images

Figure CN121064629A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of resin gears, and particularly relates to a low-friction composite gear, a preparation method thereof and application thereof. BACKGROUND
[0002] A resin gear is a kind of transmission component made of a high polymer material, which is widely used in the fields of automobiles, household appliances, medical devices, office equipment and the like. Compared with a traditional metal gear, the resin gear has the advantages of light weight, corrosion resistance, good self-lubricating property, low running noise, low cost and the like, and can reduce the wear of a matching component, and performs excellently in a light load, high speed or silent scene.
[0003] According to the material type, the resin gear can be classified into polyamide, polyformaldehyde, polycarbonate and the like. Among them, the polyamide gear has a significant application advantage due to its excellent wear resistance, fatigue resistance and mechanical strength and the like. Among the polyamide materials, poly(lauryl lactam) performs better than the rest of the polyamide materials in a humid or oily environment due to its low water absorption, good dimensional stability and chemical resistance; in addition, due to the low friction coefficient, the intermeshing operation is stable, so it is more suitable for a precision transmission system. However, the use of poly(lauryl lactam) also has certain limitations, because it can withstand a lower maximum load, and has poor thermal conductivity, and is prone to thermal deformation under high temperature or high load working conditions, so that its application in the high-power transmission field is limited.
[0004] A patent application file with the application publication number CN119708829A discloses a glass fiber reinforced PA12-PA6T composite material and a preparation method thereof, in which a silane modified glass fiber component is introduced into the poly(lauryl lactam) raw material, and is melt extruded together with poly(hexamethylene terephthalamide) resin and other additive components to obtain the composite material; the glass fiber has good interfacial compatibility with the resin system after being modified by the silane, and the mechanical properties of the prepared composite material are significantly improved.
[0005] Although the above-mentioned application material enhances the compatibility of the fiber and the matrix and the mechanical properties of the composite system by modifying the glass fiber, because the glass fiber itself has poor thermal conductivity, the gear prepared therefrom is prone to local heat accumulation during operation, thereby shortening the service life. Therefore, it is necessary to develop a low-friction composite gear which has high load capacity and improved thermal conductivity at the same time. SUMMARY
[0006] In view of the above problems, in order to further improve the load capacity of the composite gear and improve the thermal conductivity thereof at the same time, the application provides a low-friction composite gear, a preparation method thereof and application thereof.
[0007] In a first aspect, the application provides a low-friction composite gear, which is prepared by mixing raw materials in the following proportions: 50-60 parts of poly(lauryl lactam), 15-20 parts of polyformaldehyde, 2-3 parts of a compatibilizer, 2-3 parts of a thermally conductive fiber, 0.3-0.4 parts of a coupling agent, 0.1-0.2 parts of a crystallization agent, and 0.01-0.02 parts of an antioxidant; The preparation steps of the thermally conductive fiber include the following steps: S01. Take poly(ether ether ketone) fibers, treat them in an etching solution, then wash them to neutral, and dry them to obtain etched fibers; S02. Mix gelatin, fatty alcohol polyoxyethylene ether, and water, heat and stir them, then add m-cresol, poly(hexamethylene adipamide), and nano-aluminum oxide, and disperse them to obtain a sol solution; S03. Take the etched fibers, immerse them in the sol solution, and dry them to obtain thermally conductive fibers; The crystallization agent is obtained by a polycondensation reaction of dichlorobenzene, sodium sulfide, and a biphenyl derivative; The poly(ether ether ketone) fibers have an aspect ratio of (100-200):1.
[0008] By using the above technical solution, the crystallization agent is a crystalline oligomer with polyphenylene sulfide segments, which is obtained by polycondensation of p-dichlorobenzene, sodium sulfide, and a biphenyl derivative. The crystallization agent is mixed and melted with poly(lauryl lactam) and polyformaldehyde in the base component. During the cooling and crystallization stage, the crystallization agent crystallizes first and forms a primary crystal nucleus structure. Poly(lauryl lactam) and polyformaldehyde, which have crystalline properties, continue to crystallize around the primary crystal nucleus. After cooling, a high-crystalline composite gear product is obtained. The high-density crystal arrangement enhances the mechanical properties of the gear material and improves the load capacity of the gear. The thermally conductive fiber with a poly(ether ether ketone) structure as a structural support can inhibit the brittle fracture behavior of the high-crystalline gear material through a fiber toughening mechanism. In the sol solution component, nano-aluminum oxide acts as a thermal conductor. By immersing and repeatedly coating, a high-thermal-conductivity skin structure is formed on the surface of the poly(ether ether ketone). During the cooling stage of the gear component, the thermally conductive fiber with a "skin-core" structure is distributed between the "island-in-sea" structure composed of crystal and amorphous regions in the resin matrix. By bridging the adjacent resin matrix crystalline regions, it constructs a thermal conduction channel to assist in heat dissipation and avoid heat accumulation damage to the gear assembly.
[0009] Further, in step S01, the preparation steps of the etching solution are as follows: mix concentrated nitric acid with a mass concentration of 65%-68% and concentrated sulfuric acid with a mass concentration of 95%-98%, and obtain the etching solution in a cold water bath. The volume ratio of the concentrated nitric acid to the concentrated sulfuric acid used is (4-5):1.
[0010] By adopting the technical scheme, the mixed concentrated acid treatment can promote the roughening of the surface of the polyether ether ketone fiber, and in the subsequent sol solution immersion process, the surface layer of the polyether ether ketone fiber can be in full contact with the sol solution, so that the glue hanging treatment is facilitated and the adhesion of the skin layer structure to the polyether ether ketone is improved.
[0011] Further, in the step S02, the proportions of the gelatin, the fatty alcohol polyoxyethylene ether, the water, the m-toluenol, the polyhexamethylene adipamide and the nano-aluminum oxide are (1-1.2) g:(0.2-0.3) g:5 ml:(50-60) ml:(5-7) g:(2-3) g. The viscosity of the sol solution is 3.8-5.1 cP.
[0012] By adopting the technical scheme, the sol solution with a certain adhesion to the polyether ether ketone can be obtained. In the sol solution, the components such as the gelatin can improve the viscosity of the glue solution, so that the glue hanging treatment of the polyether ether ketone is facilitated. The polyhexamethylene adipamide can improve the stability of the heat-conducting fiber in the system and reduce the influence of phase separation on the heat-conducting fiber. The added nano-aluminum oxide can promote the formation of a high-thermal-conductivity skin layer structure on the surface of the polyether ether ketone fiber after the glue solution is solidified.
[0013] Further, the preparation step of the crystallizing agent includes the following steps: mixing p-dichlorobenzene, sodium sulfide and a biphenyl derivative, dispersing, then adding a catalyst promoter and reacting by increasing the temperature, extracting the precipitate after quenching by adding acetic acid, and then washing and drying to obtain the crystallizing agent. The mass ratio of the p-dichlorobenzene, the sodium sulfide, the biphenyl derivative and the catalyst promoter is (14.5-15.3):(7.2-7.7):(0.7-0.8):(0.2-0.3). The temperature increasing reaction is: increasing the temperature to 150-175℃ for 0.8-1h, and then continuously increasing the temperature to 200-225℃ for 1.2-1.5h. The structure formula of the biphenyl derivative is: Among them, R / R' is selected from one of a chlorine atom, a bromine atom and a methoxy group. The catalyst promoter is one of anhydrous sodium acetate and sodium benzoate.
[0014] By adopting the technical scheme, the p-dichlorobenzene, the sodium sulfide and the biphenyl derivative undergo nucleophilic substitution reaction under the action of the catalyst promoter, and a polymeric structure with a polyphenylene sulfide chain segment is obtained by condensation. By adjusting the reaction conditions, an oligomeric product can be obtained. The biphenyl derivative introduced in the reaction can promote the ordering of the molecular chain of the oligomeric product and the cooling crystallization behavior of the crystallizing agent through the effect of its double benzene ring structure, so that the crystallizing agent can crystallize faster.
[0015] In a second aspect, the application provides a preparation method of a low-friction composite gear, comprising the following steps: The polyformaldehyde is mixed with a crystal former, an antioxidant and a coupling agent, then poly(lauryl lactam) and a compatible agent are added, and a crude product is obtained after extrusion and injection molding through a die, and the crude product is heat treated to obtain the low-friction composite gear. The die temperature for the extrusion treatment is 210-225°C, the motor speed is 10-15 rpm, and the pressure is 50-100 bar. The injection pressure for the injection treatment is 80-100 MPa, and the extrusion speed is 120-150 mm / s.
[0016] As a general inventive concept, the application also provides the use of the low-friction composite gear prepared by the above preparation method in a resin gear.
[0017] Compared with the prior art, the application has the following beneficial effects: 1. The application prepares an oligomer crystal former with a polyphenylene sulfide chain segment, which acts as a primary crystal nucleus during the cooling process of the composite gear and promotes the crystallization of poly(lauryl lactam) and polyformaldehyde in the raw material components, finally obtaining a composite gear product with excellent mechanical properties.
[0018] 2. The application also prepares a heat-conducting fiber with a "core-sheath" structure, which is used in combination with the crystal former to improve the problem of easy brittleness of the gear part caused by high crystallization modification through fiber toughening; the poly(ether ether ketone) fiber in the core layer acts as a support for the heat-conducting fiber sheath structure, and the surface layer is subjected to etching, roughening and glue coating to obtain a high-heat-conducting sheath structure, which can connect adjacent resin cooling crystallization zones and construct a heat-conducting channel when mixed with the remaining components, thereby avoiding heat accumulation in the gear.
[0019] 3. The composite gear prepared by using the crystal former in combination with the heat-conducting fiber has a crystallinity of 67.9% and a thermal conductivity of ≥3.34 W·(m·K) -1 , and excellent mechanical strength. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 DSC melting curves of non-isothermal crystallization of the composite gear samples of Examples 1-2 and Comparative Examples 1-2 of the application.
[0021] Figure 2 Crystallinity data of the composite gear samples of Examples 1-2 and Comparative Examples 1-2 of the application.
[0022] Figure 3 Thermal conductivity data of the composite gear samples of Examples 1-4 and Comparative Example 1-2 of the application. DETAILED DESCRIPTION
[0023] The technical solutions of the present application will be explained in detail below with reference to several representative embodiments of the present application.
[0024] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0025] The raw materials used in the examples and comparative examples of the present application are described as follows: Polyether ether ketone fiber, aspect ratio (100-200): 1; Gelatin, industrial grade; Nano-aluminum oxide, Al2O3wt%≥99.9, average particle size 200-300 nm; Polyhexamethylene adipamide, average molecular weight 12000-15000; Polyformaldehyde, average molecular weight 30000-45000; Polylauric lactam, average molecular weight 50000-75000.
[0026] Table 1 Composite gear injection molding, extrusion process parameters of examples 1-4 and comparative examples 1-2 Preparation example 1 Take 100 ml N-methyl pyrrolidone and bubble with nitrogen for 10 min, then heat to 75℃, then add 14.5 g of p-dichlorobenzene, 7.2 g of sodium sulfide and 0.7 g of 4,4'-dichlorobiphenyl, then add 0.2 g of anhydrous sodium acetate, adjust the magnetic stirring speed to 200 rpm, then raise the system temperature to 150℃, maintain for 0.8 h, then continue to raise the system temperature to 200℃, maintain for 1.2 h, then stop heating, add 0.5 g of acetic acid to quench the reaction, naturally cool to 70℃, then extract with acetone to obtain a precipitate, wash with 60℃ hot water and ethanol for 3 times each, then transfer the precipitate to an oven and dry at 50℃ to obtain a crystallization agent.
[0027] Mix 40 ml of concentrated nitric acid with a mass concentration of 65% with 10 ml of concentrated sulfuric acid with a mass concentration of 98%, and prepare a cold water bath.
[0028] Take 5 g of polyether ether ketone fiber, ultrasonicate in acetone for 5 min, dry, then immerse in 50 ml of etching solution, maintain the temperature at 35℃ for 2 min, then transfer to 0.5 mol / l sodium hydroxide solution and continue to soak for 5 min, finally wash with water to neutral, then dry in an oven at 60℃ for 2 h to obtain etched fiber.
[0029] Preparation example 2 Take 100 ml N-methyl pyrrolidone nitrogen bubbling 20 min after warming to 80℃, then add 15 g p-dichlorobenzene, 7.5 g sodium sulfide and 0.72 g 4-bromo-4'- methoxy biphenyl, then add 0.25 g sodium benzoate, adjust the magnetic stirring speed to 300 rpm, then raise the system temperature to 175℃, maintain 1 h, then continue to raise the system temperature to 210℃, maintain 1.2 h, then stop heating, add 0.5 g acetic acid to quench the reaction, naturally cool to 70℃, then add acetone to extract the precipitate, wash with 60℃ hot water and ethanol each 3 times, then transfer the precipitate to an oven at 50℃ to dry, to obtain the crystallization agent.
[0030] Take 50 ml of 68% concentrated nitric acid and 10 ml of 95% concentrated sulfuric acid, and mix them in a cold water bath.
[0031] Take 5 g of polyether ether ketone fiber, ultrasonic in acetone for 10 min, then immerse in 60 ml of etching solution at 40℃ for 3 min, then transfer to 0.5 mol / l sodium hydroxide solution and continue to soak for 5 min, finally wash with water to neutral, then dry in an oven at 60℃ for 2 h, to obtain the etched fiber.
[0032] Preparation Example 3 Take 100 ml N-methyl pyrrolidone nitrogen bubbling 30 min after warming to 80℃, then add 15.3 g p-dichlorobenzene, 7.7 g sodium sulfide and 0.8 g 4,4'-dibromobiphenyl, then add 0.3 g sodium benzoate, adjust the magnetic stirring speed to 300 rpm, then raise the system temperature to 175℃, maintain 1 h, then continue to raise the system temperature to 225℃, maintain 1.5 h, then stop heating, add 0.6 g acetic acid to quench the reaction, naturally cool to 80℃, then add acetone to extract the precipitate, wash with 60℃ hot water and ethanol each 3 times, then transfer the precipitate to an oven at 50℃ to dry, to obtain the crystallization agent.
[0033] Take 45 ml of 65% concentrated nitric acid and 10 ml of 98% concentrated sulfuric acid, and mix them in a cold water bath.
[0034] Take 5 g of polyether ether ketone fiber, ultrasonic in acetone for 10 min, then immerse in 75 ml of etching solution at 40℃ for 3 min, then transfer to 0.5 mol / l sodium hydroxide solution and continue to soak for 5 min, finally wash with water to neutral, then dry in an oven at 60℃ for 3 h, to obtain the etched fiber.
[0035] Example 1 The preparation steps of the heat-conducting fiber in this example are as follows: Take 1 g gelatin, 0.2 g fatty alcohol polyoxyethylene ether and 5 ml deionized water, adjust the magnetic stirring speed to 100 rpm, 60℃ treatment 5 min, then add 50 ml m-toluenol and 5 g polyhexamethylene adipate, add 0.5 g Tween 20 and 2 g nano alumina, continue constant temperature stirring, until the system viscosity reaches 3.8 cP, stop heating to get sol liquid, then take 3 g etching fiber in the sol liquid, dip for 3 s, then take out, 50℃ in the oven for 5 min, repeat the operation 5 times, then dry, get the thermal conductive fiber.
[0036] The preparation steps of the low-friction composite gear in this example are as follows: Take 1500 g polyformaldehyde and 10 g crystal former, 1 g antioxidant 1010 and 30 g titanate coupling agent (TC-131) mixed, placed in the mixing machine for 5 min, then transferred to the twin screw extruder, 5000 g poly lauryl lactam and 200 g compatible agent (POE-g-MAH) are added from the main feeding port, mixed for 10 min, then 200 g thermal conductive fiber is added from the side feeding port, continue to process for 30 min to get the melt mixture, the mixture is injection molded to get the rough product, then heat treated in the 80℃ oven for 2 h, deburring and polishing, then get the product.
[0037] The crystal former and etching fiber in this example are prepared by preparation example 1.
[0038] Example 2 The preparation steps of the thermal conductive fiber in this example are as follows: Take 1 g gelatin, 0.2 g fatty alcohol polyoxyethylene ether and 5 ml deionized water, adjust the magnetic stirring speed to 100 rpm, 60℃ treatment 5 min, then add 50 ml m-toluenol and 5 g polyhexamethylene adipate, add 0.5 g Tween 20 and 2 g nano alumina, continue constant temperature stirring, until the system viscosity reaches 3.8 cP, stop heating to get sol liquid, then take 3 g etching fiber in the sol liquid, dip for 3 s, then take out, 50℃ in the oven for 5 min, repeat the operation 5 times, then dry, get the thermal conductive fiber.
[0039] The preparation steps of the low-friction composite gear in this example are as follows: Take 1500 g polyformaldehyde and 10 g crystal former, 1 g antioxidant 1010 and 30 g titanate coupling agent (TC-131) mixed, placed in the mixing machine for 5 min, then transferred to the twin screw extruder, 5000 g poly lauryl lactam and 200 g compatible agent (POE-g-MAH) are added from the main feeding port, mixed for 10 min, then 200 g thermal conductive fiber is added from the side feeding port, continue to process for 30 min to get the melt mixture, the mixture is injection molded to get the rough product, then heat treated in the 80℃ oven for 2 h, deburring and polishing, then get the product.
[0040] The crystal forming agent and the etching fiber in this example were prepared according to Preparation Example 2.
[0041] Example 3 The preparation steps of the heat-conducting fiber in this example are as follows: Take 1.2 g of gelatin, 0.3 g of fatty alcohol polyoxyethylene ether, and 5 ml of deionized water, adjust the magnetic stirring speed to 150 rpm, treat at 70°C for 10 min, then add 60 ml of m-cresol and 7 g of polyhexamethylene adipamide, add 0.6 g of Tween 20 and 3 g of nano-alumina, continue to stir at constant temperature, stop heating when the system viscosity reaches 5.1 cP to obtain a sol solution, then take 4 g of etching fiber and immerse it in the sol solution for 5 s, then take it out and treat it in an oven at 50°C for 10 min, repeat the operation 5 times and then dry to obtain the heat-conducting fiber.
[0042] The preparation steps of the low-friction composite gear in this example are as follows: Take 2000 g of polyformaldehyde, 15 g of crystal forming agent, 2 g of antioxidant 1010, and 40 g of titanate coupling agent (TC-131), mix them in a mixer for 20 min, then transfer them to a twin-screw extruder, add 5500 g of poly-laurolactam and 250 g of compatibility agent (POE-g-MAH) from the main feeding port, mix for 20 min, then add 200 g of heat-conducting fiber from the side feeding port, continue to mix for 40 min to obtain a molten mixture, mold the mixture to obtain a rough product, then heat treat it in an oven at 90°C for 2 h, deburr and polish it to obtain the final product.
[0043] The crystal forming agent and the etching fiber in this example were prepared according to Preparation Example 3.
[0044] Example 4 The preparation steps of the heat-conducting fiber in this example are as follows: Take 1.2 g of gelatin, 0.3 g of fatty alcohol polyoxyethylene ether, and 5 ml of deionized water, adjust the magnetic stirring speed to 200 rpm, treat at 70°C for 10 min, then add 60 ml of m-cresol and 7 g of polyhexamethylene adipamide, add 0.6 g of Tween 20 and 3 g of nano-alumina, continue to stir at constant temperature, stop heating when the system viscosity reaches 4.8 cP to obtain a sol solution, then take 4 g of etching fiber and immerse it in the sol solution for 5 s, then take it out and treat it in an oven at 50°C for 10 min, repeat the operation 6 times and then dry to obtain the heat-conducting fiber.
[0045] The preparation steps of the low-friction composite gear in this example are as follows: Take 2000 g of polyformaldehyde and mix 20 g of crystallization agent, 2 g of antioxidant 1010 and 40 g of titanate coupling agent (TC-131) in a mixer for 20 min, then transfer to a twin-screw extruder, add 6000 g of poly-laurolactam and 300 g of a compatibilizer (POE-g-MAH) from the main feeding port, mix for 20 min, then add 300 g of thermally conductive fiber from the side feeding port, continue to mix for 40 min to obtain a molten mixture, then injection mold the mixture to obtain a rough product, then heat treat in an oven at 90°C for 3 h, deburring and polishing to obtain the final product.
[0046] The crystallization agent in this example is prepared according to Preparation Example 2, and the etched fiber is prepared according to Preparation Example 3.
[0047] Comparative Example 1 The difference between this comparative example and Example 1 is that the same amount of calcium carbonate powder is used instead of the crystallization agent to prepare the low-friction composite gear.
[0048] The calcium carbonate powder has an average particle size of 10-25 microns.
[0049] The remaining steps are the same as in Example 1.
[0050] Comparative Example 2 The difference between this comparative example and Example 1 is that the same amount of glass fiber is used instead of the thermally conductive fiber to prepare the low-friction composite gear.
[0051] The glass fiber has an aspect ratio of 100:1.
[0052] The remaining steps are the same as in Example 1.
[0053] Performance testing 1. Appearance performance test Table 2. Appearance performance test items of composite gears in Examples 1-4 and Comparative Examples 1-2 The test results are shown in Table 3.
[0054] Table 3. Appearance performance test results of composite gears in Examples 1-4 and Comparative Examples 1-2 By analyzing Examples 1-4 and Comparative Examples 1-2 and combining Tables 2 and 3, it can be seen that the test groups in the examples perform better than the comparative examples in terms of mechanical properties; the composite gears prepared according to the example scheme have higher strength and modulus, and can withstand higher maximum load under the premise of maintaining a low friction coefficient, indicating that the composite gear products prepared can still maintain good dimensional stability under higher load torque; among all the example groups, Examples 1 and 2 have superior comprehensive performance.
[0055] 2. Crystallinity test Referring to the relevant test methods in national standard GB / T19466.3-2004, composite gear samples from Examples 1-2 and Comparative Examples 1-2 were subjected to DSC tests for non-isothermal crystallization. The test results are as follows: Figure 1 As shown, the enthalpy of fusion of polylaurolactam in each group of samples was calculated. According to the formula: The crystallinity of polylaurolamide in each group of samples was calculated.
[0056] in, Crystallinity; The enthalpy of melting of polylaurolactam; The theoretical enthalpy of polylaurolactam; Mass fraction of polylaurolamide.
[0057] Crystallinity test results are as follows Figure 2 As shown.
[0058] Analysis of Examples 1-2 and Comparative Examples 1-2 and in combination Figure 1 and Figure 2 It can be concluded that the appearance of the melt peak position in the melt curves of Examples 1-2 lags behind that of Comparative Examples 1-2, indicating that the samples of Examples 1-2 have higher crystalline melting temperatures and more complete crystalline structures. Figure 2 The crystallinity test results can further verify the promoting effect of the combination of crystallizing agent and thermally conductive fiber on the crystallization of polymer in the sample. In contrast, Comparative Example 1 uses calcium carbonate micro powder instead of organic crystallizing agent in the raw material components. Due to potential problems such as dispersibility and compatibility of inorganic components in the system, its promoting effect on the crystallization of polymer components is not good. In Comparative Example 2, the combination of glass fiber and crystallizing agent is not good, resulting in the crystallization performance of the composite gear product not being as good as that of the example scheme.
[0059] 3. Thermal conductivity Referring to the relevant test methods in the national standard GB / T3139-2005, the thermal conductivity of composite gear samples from Examples 1-4 and Comparative Examples 1-2 was tested. The test results are as follows: Figure 3 As shown.
[0060] Analysis of Examples 1-4 and Comparative Examples 1-2 in conjunction with Figure 3It can be concluded that the thermal conductivity of the composite gear products of the embodiments and the comparative example 1 is greatly improved due to the introduction of the thermal conductive fibers in the system, and both of them show better effects than the comparative example 2; the comparative example 1 has a low crystallization perfection and lacks ordered and heat-conductive crystal region structure, so the addition of the thermal conductive fibers only slightly improves the thermal conductivity of the product; in contrast, the comparative example 2 uses glass fibers with poor thermal conductivity as the fiber reinforcement instead of the thermal conductive fibers, and cannot construct a good heat-conductive channel in the system, so the product has poor thermal conductivity, and the composite gear prepared has the risk of heat accumulation and damage to the gear during use.
[0061] Although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art can make modifications to the technical solutions recorded in the foregoing embodiments or make equivalent replacements to part of the technical features, and any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A low friction composite gear, characterized by, It is prepared by mixing raw materials including the following mass parts: 50-60 parts of polylauramide, 15-20 parts of polyformaldehyde, 2-3 parts of a compatible agent, 2-3 parts of a heat-conducting fiber, 0.3-0.4 parts of a coupling agent, 0.1-0.2 parts of a crystallization agent, and 0.01-0.02 parts of an antioxidant; The preparation step of the heat-conducting fiber comprises the following steps: S01. Taking polyether ether ketone fibers, treating them in an etching solution, then washing them to neutral, and drying them to obtain etched fibers; S02. Mixing gelatin, fatty alcohol polyoxyethylene ether, and water, stirring them at elevated temperature, then adding m-methylphenol, polyhexamethylene adipamide, and nano-aluminum oxide, and dispersing to obtain a sol solution; S03. Taking the etched fibers, immersing them in the sol solution, and drying them to obtain heat-conducting fibers; The crystallization agent is obtained by a polycondensation reaction of p-dichlorobenzene, sodium sulfide, and a biphenyl derivative.
2. A low friction composite gear according to claim 1, wherein, In the step S01, the preparation step of the etching solution is as follows: mixing concentrated nitric acid with a mass concentration of 65%-68% and concentrated sulfuric acid with a mass concentration of 95%-98%, and obtaining the etching solution in a cold water bath; The volume ratio of the concentrated nitric acid to the concentrated sulfuric acid used is (4-5):
1.
3. A low friction composite gear according to claim 1, wherein In the step S02, the proportions of gelatin, fatty alcohol polyoxyethylene ether, water, m-methylphenol, polyhexamethylene adipamide, and nano-aluminum oxide used are (1-1.2) g:(0.2-0.3) g:5 ml:(50-60) ml:(5-7) g:(2-3) g; The viscosity of the sol solution is 3.8-5.1 cP.
4. A low friction composite gear according to claim 1, wherein The preparation step of the crystallization agent comprises the following steps: mixing p-dichlorobenzene, sodium sulfide, and a biphenyl derivative, dispersing, then adding a catalyst promoter, reacting at elevated temperature, adding acetic acid to quench the reaction, extracting to obtain a precipitate, and then washing and drying to obtain the crystallization agent.
5. A low friction composite gear according to claim 4, wherein The mass ratio of the p-dichlorobenzene, sodium sulfide, biphenyl derivative, and catalyst promoter used is (14.5-15.3):(7.2-7.7):(0.7-0.8):(0.2-0.3). The structure of the biphenyl derivative is as follows: wherein R / R' is selected from one of a chlorine atom, a bromine atom, and a methoxy group; The catalyst promoter is one of anhydrous sodium acetate and sodium benzoate.
6. A low friction composite gear according to claim 4, wherein, The reaction at elevated temperature is as follows: increasing the temperature to 150-175°C for 0.8-1 h, and then continuously increasing the temperature to 200-225°C for 1.2-1.5 h.
7. A method of producing a low-friction composite gear, characterized by, The preparation method comprises the following steps: Mixing polyformaldehyde with the crystallization agent, antioxidant, and coupling agent, then adding polylauramide and a compatible agent, extruding through a die, and injection molding to obtain a crude product, and then heat treating the crude product to obtain the low-friction composite gear.
8. A method of producing a low friction composite gear according to claim 7, wherein The die temperature for the extrusion treatment is 210-225°C, the motor speed is 10-15 rpm, and the pressure is 50-100 bar.
9. The method of claim 7, wherein the low friction composite gear is prepared by the steps of: The injection pressure for the injection molding treatment is 80-100 MPa, and the extrusion speed is 120-150 mm / s.
10. Application of the low-friction composite gear prepared by the preparation method of any one of claims 7-9 in a resin gear.
Citation Information
Patent Citations
Glass fiber reinforced PA12-PA6T composite material and preparation method thereof
CN119708829A
Continuous fiber composite high thermal conductive material and processing technology thereof
CN104292817A
Low-friction wear-resistant composite material with microfibrillated structure as well as preparation method and application of low-friction wear-resistant composite material
CN112300573A
Glass fiber reinforced high-strength engineering plastic and preparation method thereof
CN112457659A
Low-friction wear-resistant composite material with bicontinuous microfibrillated structure as well as preparation method and application of low-friction wear-resistant composite material
CN114907694A